2013
DOI: 10.1111/gcbb.12106
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and nitrogen dynamics in bioenergy ecosystems: 2. Potential greenhouse gas emissions and global warming intensity in the conterminous United States

Abstract: This study estimated the potential emissions of greenhouse gases (GHG) from bioenergy ecosystems with a biogeochemical model AgTEM, assuming maize (Zea mays L.), switchgrass (Panicum virgatum L.), and Miscanthus (Miscanthus 9 giganteus) will be grown on the current maize-producing areas in the conterminous United States. We found that the maize ecosystem acts as a mild net carbon source while cellulosic ecosystems (i.e., switchgrass and Miscanthus) act as mild sinks. Nitrogen fertilizer use is an important fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 75 publications
1
31
0
Order By: Relevance
“…Concerns about global warming and dependence on foreign fossil fuels in the United States triggered a search for more sustainable sources of energy (Congress, ; Bang, ). US legislators mandated production of at least 36 billion gallons (136 Gl) of biofuels by 2022, of which 21 billion (80 Gl) should come from non‐cornstarch feedstock (Gelfand et al ., ; Qin et al ., ). Switchgrass ( Panicum virgatum L.), a perennial grass native to the North American prairie, is sought as an alternative bioenergy source (Lee et al ., ; Sanderson & Adler, ).…”
Section: Introductionmentioning
confidence: 97%
“…Concerns about global warming and dependence on foreign fossil fuels in the United States triggered a search for more sustainable sources of energy (Congress, ; Bang, ). US legislators mandated production of at least 36 billion gallons (136 Gl) of biofuels by 2022, of which 21 billion (80 Gl) should come from non‐cornstarch feedstock (Gelfand et al ., ; Qin et al ., ). Switchgrass ( Panicum virgatum L.), a perennial grass native to the North American prairie, is sought as an alternative bioenergy source (Lee et al ., ; Sanderson & Adler, ).…”
Section: Introductionmentioning
confidence: 97%
“…In terms of GHG mitigation, many studies have shown that biofuel feedstock production under perennial C 4 grasses such as miscanthus ( Miscanthus × giganteus ) and switchgrass ( Panicum virgatum L.) has a much larger CO 2 sink potential and lower GHG emissions when compared with annual crops and C 3 grass systems in the USA (Qin et al, ). This is in large part due to miscanthus and switchgrass, both having a much larger soil organic carbon (SOC) sequestration potential via CO 2 capture by photosynthesis and storage of C in the soil (Shrestha et al, ; Don et al, ; Guzman & Lal, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, criticism of the production of food and feed crops grown especially for energy purposes, such as maize or rapeseed, has motivated the search for high-yielding non-food energy crops. In recent years, the establishment of perennial crops has emerged as a very viable option mainly due to their comparative ecological advantages over annual energy crops [27,28,32]. Among these, the C4 grasses miscanthus and switchgrass combine the potential to deliver high biomass yield and ability to grow under a wide range of climatic conditions [21].…”
Section: Introductionmentioning
confidence: 99%